Symphony no. 5 in D minor, op. 47 [compact disc] - Shostakovich, Dmitriĭ Dmitrievich, 1906-1975 (Pittsburgh live!, 2017)
In his fascinating and scholarly music notes, Maestro Honeck gives listeners great insight into the history of both pieces, and describes how he conducts and interprets each.